Study on the Effects and Mechanisms of Action of Biological Enzymes on the Quality of Summer Rock Tea Extract - Zixuan Wang; Bo Yang; Peng Zhou; Guang Yang; Zhijun Zhao (Applied Sciences)
The gallated catechin content in Wuyi Rock Tea is higher in the summer, leading to a more bitter and less desirable taste. Here, tannase, tyrosinase, and laccase were used to treat summer Rougui Wuyi Rock Tea extracts. The effects of single and combined enzymes on the taste of the tea extracts and their mechanisms of action were analyzed. Compared with the no-enzyme-treated sample, the sensory score results showed that tannase was the most effective, increasing the bitterness and astringency scores by 113.9% and 255.3%, respectively. Among the combined enzyme treatments, the samples treated with tannase and tyrosinase yielded the best sensory scores, with bitterness and astringency scores increasing by 141.2% and 289.0%, respectively. Data obtained using an electronic tongue confirmed the role of these enzymes, showing that, in addition to bitterness and astringency, enzyme treatment also influenced the bitterness aftertaste and astringency aftertaste, as well as its sourness and sweetness. Further product analysis revealed that tannase hydrolyzes the ester bonds on the gallacyl groups in gallated catechins, converting them to non-gallated catechins, while tyrosinase and laccase oxidize the phenolic hydroxyl groups on catechins to form o-quinone, leading to the production of theaflavins and improved tea quality. This study presents an effective approach to improving the quality of summer tea using biological enzymes.